2019
DOI: 10.3390/jcs3020052
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Degradation During Melt Processing of PLA/Biosilicate® Composites

Abstract: Poly (lactic acid) (PLA)/bioactive composites are emerging as new biomaterials since it is possible to combine stiffness, mechanical resistance, and bioactive character of the bioglasses with conformability and bioabsorption of the PLA. In this study, PLA/Biosilicate® composites were prepared using a melt-processing route. The processability and properties were evaluated aiming to produce composites with bioactive properties. Two different PLA (PLA 2003D and PLA 4043D) were tested with the addition of 1 wt. % … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 25 publications
(52 reference statements)
5
43
0
1
Order By: Relevance
“…Blaker et al [14] have noted premature degradation of the PLA/45S5 during melt-compounding, and they attributed this to the liberation of counterions of 45S5 that hasten thermal degradation reactions in PLA matrix [14]. More recently, Backes et al [29] observed the same behavior for PLA/Biosiolicate ® composites during similar processing conditions. The results of zeta potential for HA show a considerable liberation of ions that might contribute to catalyzing the polymer degradation during thermal processing.…”
Section: Resultsmentioning
confidence: 91%
“…Blaker et al [14] have noted premature degradation of the PLA/45S5 during melt-compounding, and they attributed this to the liberation of counterions of 45S5 that hasten thermal degradation reactions in PLA matrix [14]. More recently, Backes et al [29] observed the same behavior for PLA/Biosiolicate ® composites during similar processing conditions. The results of zeta potential for HA show a considerable liberation of ions that might contribute to catalyzing the polymer degradation during thermal processing.…”
Section: Resultsmentioning
confidence: 91%
“…The effect of the fungi on the structure was evidenced by the disappearance of the shoulder and the determined thermal events are shifted indicating presence of smaller molecules which crystalize leading to higher crystallinity. Backes et al [63] observed a similar phenomenon during the study of PLA/Biosilicate composites and concluded that the crystallization of PLA occurs easier in degraded systems with greater mobility. This outcome can support the hypothesis that after biodegradation in the presence of the two fungi, the chains of PLA/PEG/R became shorter in accordance with GPC results.…”
Section: Samples Codementioning
confidence: 70%
“…2,32 Despite its ongoing evolution process, PLA alone lacks bioactivity and exhibits limited interaction and integration with the tissue host. 33,34 Therefore, the development and evaluation of mechanical, thermal, rheological, and biological properties of PLA bioactive composites is an important step to consolidate the PLA along with AM.…”
Section: Resultsmentioning
confidence: 99%
“…Surface properties play a significant role in cell attachment and proliferation; therefore, suitable wettability is beneficial for cell interaction with materials. 15,34 The results of relative cell viability using PLA and PLA/TCP extracts are exhibited in Figure 5(b), and they were corrected using the cell with α-MEM as blank. They show that the PLA and PLA5TCP extracts presented behaviors similar to that of the control for both timepoints analyzed, exemplifying that the samples do not release harmful debris, which might reduce cell viability.…”
Section: Resultsmentioning
confidence: 99%